Russia's power projection into Syria and its interactions with local states. (5th July 2022) - Alim, Eray
Abstract : By analysing Russia's engagements with Israel and Turkey in Syria, this article shows what can happen when an external great power interacts with local states. Russia has been able to ensure, sometimes though restrictive and punitive measures, that Turkey and Israel don't harm its interests in the region. Abstract: By analysing Russia's engagements with Israel and Turkey in the Syrian theatre, this article sheds light on the kinds of interactions that may occur between an external great power and local states following the former's projection of power into the latter's region. The literature on power projection examines interactions between regional and extra-regional actors in the context of competition between great powers, thus overlooking interactions between great powers and non-great powers. Other literature, such as that on coercive diplomacy, does deal with this neglected issue, but it treats local states as the great power's target states. This, however, need not be the case, since great powers may engage local states while pursuing wholly different goals in a region. As this article illustrates, although Israel and Turkey have not been Russia's target states, Russia has frequently interacted with them to ensure that they refrain from acts harmful to its interests in Syria. Russia has succeeded in this endeavour, as local states have mostly complied with Russia's rules and restrictions while operating in Syria. When this was not the case, Russia introduced restrictive or punitive measures against Israel and Turkey, which enabled Moscow to keep the local environment conductive to its interests.